222k views
0 votes
Simplify √28 . √27 . √5

Simplify 2√5 + 3√5 - √5

Which expression is equal to 2√28 - 5√63

A) -√7
B) -37√7
C) √7
D) -11√7

Thank you

User Aarelovich
by
4.5k points

2 Answers

5 votes

Answer:

1. 6√105

2. 4√5

3. D

Explanation:

Math is an interesting invention.

User Louis Etienne
by
5.4k points
6 votes

Answer:

Simplify
√(28) * √(27) * √(5)

Observe that all roots are similar, because they are square roots.

To simplify this products, we can write only one root and multiply all sub-radical numbers, as follows


√(28) * √(27) * √(5)=√(28 * 27 * 5)

It's better to maintain the product as factors, so, let's express each number in a power


√(28) * √(27) * √(5)=√(28 * 27 * 5)=\sqrt{2^(2) * 7 * 3^(2) * 3 * 5 }

Then, all square powers can go out the root


\sqrt{2^(2) * 7 * 3^(2) * 3 * 5 }=2* 3 √(105)=6 √(105)

Therefore, the answer here is
6√(105)

Simplify
2√(5)+3√(5)-√(5)

Observe that all roots are exactly the same, we proceed to sum and subtract the whole part of each term


2√(5)+3√(5)-√(5)=(2+3-1)√(5)=4√(5)

Therefore, the answer is
4√(5)

Which expression is equal to
2√(28)-5√(63)

Let's express each root in factors


2√(28)-5√(63)=2√(7 * 4) -5 √(7 * 9)

Then, we solve the root for 4 and 9


2√(7 * 4) -5 √(7 * 9)=4√(7)-15√(7)

Then, we subtract


4√(7)-15√(7)=-11√(7)

Therefore, the right answer is D.

User Claya
by
5.4k points